Microglial Activation and Connectivity in Alzheimer Disease and Aging. Issue 5 (25th August 2022) - Rauchmann, Boris‐Stephan; Brendel, Matthias; Franzmeier, Nicolai; Trappmann, Lena; Zaganjori, Mirlind; Ersoezlue, Ersin; Morenas‐Rodriguez, Estrella; Guersel, Selim; Burow, Lena; Kurz, Carolin; Haeckert, Jan; Tatò, Maia; et al.
Abstract : Objective: Alzheimer disease (AD) is characterized by amyloid β (Aβ) plaques and neurofibrillary tau tangles, but increasing evidence suggests that neuroinflammation also plays a key role, driven by the activation of microglia. Aβ and tau pathology appear to spread along pathways of highly connected brain regions, but it remains elusive whether microglial activation follows a similar distribution pattern. Here, we assess whether connectivity is associated with microglia activation patterns. Methods: We included 32 Aβ‐positive early AD subjects (18 women, 14 men) and 18 Aβ‐negative age‐matched healthy controls (10 women, 8 men) from the prospective ActiGliA (Activity of Cerebral Networks, Amyloid and Microglia in Aging and Alzheimer's Disease) study. All participants underwent microglial activation positron emission tomography (PET) with the third‐generation mitochondrial 18 kDa translocator protein (TSPO) ligand [ 18 F]GE‐180 and magnetic resonance imaging (MRI) to measure resting‐state functional and structural connectivity. Results: We found that inter‐regional covariance in TSPO‐PET and standardized uptake value ratio was preferentially distributed along functionally highly connected brain regions, with MRI structural connectivity showing a weaker association with microglial activation. AD patients showed increased TSPO‐PET tracer uptake bilaterally in the anterior medial temporal lobe compared to controls, and higher TSPO‐PET uptake was associated with cognitive impairment and dementia severity in a disease stage‐dependent manner. Interpretation: Microglial activation distributes preferentially along highly connected brain regions, similar to tau pathology. These findings support the important role of microglia in neurodegeneration, and we speculate that pathology spreads throughout the brain along vulnerable connectivity pathways. ANN NEUROL 2022;92:768–781